IMPLEMENTASI KEGIATAN OUTBOND TRAINING TERHADAP KETERAMPILAN SOSIAL SISWA TK ORBIT SURAKARTA - Dhian Riskiana Putri; Anniez Rachmawati Musslifah; Faqih Purnomosidi; Sri Ernawati (Jurnal Genta Mulia, 2025)
This research aims to determine the effect of outbound training activities on the social skills of Orbit Surakarta Kindergarten students. This research uses a quasi-experimental type of research with a one group pretest-posttest design. The respondents for this research were all 15 Orbit Surakarta Kindergarten teachers. The focus of the research is on the skills problems of early childhood students before and after being given outbound training. The targets and participants of the outbound activities were 147 Orbit Surakarta Islamic KB/TK students. Treatment in the form of outbound training activities was given to participants who had previously filled in the social skills scale with the teacher and then carried out the same thing after giving the treatment. The effect of providing outbound training activities on student skills was measured using the paired samples t-test. The results show that the Sig value. (2-tailed) is 0.000 < 0.05, which means there is an average difference between the Pre Test and Post Test results, meaning there is an influence of providing outbound training to improve social skills in Orbit Surakarta Kindergarten students.